Sistem Pendukung Keputusan Menggunakan Metode WASPAS Untuk Pemilihan Software Developer - Bagir, Muhammad; Sanwasih, Mochamad; Arisantoso, Arisantoso; Rahmadian, Jefri (FORMAT, 2025)
The advancement of information technology has driven an increased demand for competent software developers aligned with project specifications, making the selection process a strategic challenge for organizations. However, manual selection is often subjective, time-consuming, and prone to errors. Therefore, this study aims to develop a Decision Support System (DSS) based on the Weighted Aggregated Sum Product Assessment (WASPAS) method. WASPAS was chosen for its ability to integrate the strengths of the Weighted Sum Model (WSM) and Weighted Product Model (WPM) to produce decisions based on criteria weights and alternative performance. The system is designed as a web-based application to provide ease of access and usability, featuring key functionalities such as data management for criteria, alternatives, and values, as well as calculation and result presentation using the WASPAS method. The case study results indicate that Mochammad Rizal (A3) is the best alternative with the highest score of 0.8904, followed by Yosua Surojo (A4) with a score of 0.8718. Tommy Pratama (A2) ranks third with a score of 0.7101, while Gigih Prayitno (A1) occupies the last position with a score of 0.6713. System testing using the black-box testing method ensures that all features function according to the designed specifications. This study contributes a systematic solution to simplify the software developer selection process while reducing subjective bias in decision-making.